Perceived Competency of Human Resource Managers in Referral Hospitals, Ethiopia (Global Journal of Management and Business Research, 2015)
Background: Sound human resources management practices are essential for retaining effective professionals in hospitals that addressing health workforce challenges and developing the health workforce strategy of the country. Thus it is rational to assess the competency level of human resource managers found in hospitals. Objective: The overall objective of this study was to assess the competency level in human resource management in public referral hospitals found in Oromia regional state, Ethiopia. Methods: A cross-sectional survey involving 290 human resource managers of the referral hospital found in Oromia regional carried out from February to march 2012.The survey was supplemented by in-depth interview of a qualitative method. The collected data was entered into SPSS Software version 20.0, cleaned and analyzed. Descriptive analyses and Binary logistic regression were used. The results were summarized as crude and adjusted odds ratios at 95% confidence intervals.
Keywords: perceive competence; competence domains; human resource management and leadership; Jimma